The subthalamic nucleus during decision‐making with multiple alternatives. Issue 10 (15th July 2015) - Keuken, Max C.; Van Maanen, Leendert; Bogacz, Rafal; Schäfer, Andreas; Neumann, Jane; Turner, Robert; Forstmann, Birte U.
Abstract Several prominent neurocomputational models predict that an increase of choice alternatives is modulated by increased activity in the subthalamic nucleus (STN). In turn, increased STN activity allows prolonged accumulation of information. At the same time, areas in the medial frontal cortex such as the anterior cingulate cortex (ACC) and the pre‐SMA are hypothesized to influence the information processing in the STN. This study set out to test concrete predictions of STN activity in multiple‐alternative decision‐making using a multimodal combination of 7 Tesla structural and functional Magnetic Resonance Imaging, and ancestral graph (AG) modeling. The results are in line with the predictions in that increased STN activity was found with an increasing amount of choice alternatives. In addition, our study shows that activity in the ACC is correlated with activity in the STN without directly modulating it. This result sheds new light on the information processing streams between medial frontal cortex and the basal ganglia. Hum Brain Mapp 36:4041–4052, 2015. © 2015 Wiley Periodicals, Inc.